The Performance of First-Trimester Anatomy Scan: A Decision Analysis - Harper, Lorie M.; Wood, S. Lindsay; Jenkins, Sheri M.; Owen, John; Biggio, Joseph R. (American Journal of Perinatology, 2016)
Introduction First-trimester ultrasound (US) for anatomy assessment may improve anomaly detection, but it may also increase overall US utilization. We sought to assess the utility of first-trimester US for evaluation of fetal anatomy.Materials and Methods A decision analytic model was created to compare first- plus second-trimester anatomy scans to second-trimester scan alone in four populations: general, normal weight women, obese women, and diabetics. Probability estimates were obtained from the literature. Outcomes considered were number of: major structural anomalies detected, US performed, and false-positive US. Multivariable sensitivity analyses were performed to evaluate the consistency of the model with varying assumptions.Results A strategy of first- plus second-trimester US detected the highest number of anomalies but required more US examinations per anomaly detected. The addition of a first-trimester anatomy US was associated with a small increase in the false-positive US (< 10/10,000). In populations with higher anomaly prevalence and lower second-trimester US sensitivity (i.e., diabetes, obesity), the number of additional US performed per anomaly detected with the first-trimester US was < 60.Discussion In high-risk populations, a first-trimester US in addition to a second-trimester US may be a beneficial approach to detecting anomalies.
Keywords: anatomy ultrasound; first trimester; second trimester; decision analysis; sensitivity